Aviation contrail climate effects in the North Atlantic from 2016 to 2021 - Teoh, Roger; Schumann, Ulrich; Gryspeerdt, Edward; Shapiro, Marc; Molloy, Jarlath; Koudis, George S.; Voigt, Christiane; Stettler, Marc E. J. (Atmospheric Chemistry and Physics, 2022)
Around 5 % of anthropogenic radiative forcing (RF) is attributed to aviation CO2 and non-CO2 impacts. This paper quantifies aviation emissions and contrail climate forcing in the North Atlantic, one of the world’s busiest air traffic corridors, over 5 years. Between 2016 and 2019, growth in CO2 (C3:13% yr-1) and nitrogen oxide emissions (C4:5 % yr-1) outpaced increases in flight distance (C3:05 % yr-1). Over the same period, the annual mean contrail cirrus net RF (204–280 mW m-2) showed significant inter-annual variability caused by variations in meteorology. Responses to COVID-19 caused significant reductions in flight distance travelled (-66%), CO2 emissions (-71%) and the contrail net RF (-66%) compared with the prior 1-year period. Around 12 % of all flights in this region cause 80 % of the annual contrail energy forcing, and the factors associated with strongly warming/cooling contrails include seasonal changes in meteorology and radiation, time of day, background cloud fields, and engine-specific non-volatile particulate matter (nvPM) emissions. Strongly warming contrails in this region are generally formed in wintertime, close to the tropopause, between 15:00 and 04:00 UTC, and above low-level clouds. The most strongly cooling contrails occur in the spring, in the upper troposphere, between 06:00 and 15:00 UTC, and without lower-level clouds. Uncertainty in the contrail cirrus net RF (216–238 mW m-2) arising from meteorology in 2019 is smaller than the inter-annual variability. The contrail RF estimates are most sensitive to the humidity fields, followed by nvPM emissions and aircraft mass assumptions. This longitudinal evaluation of aviation contrail impacts contributes a quantified understanding of inter-annual variability and informs strategies for contrail mitigation.